GASEOUS ENVIRONMENT AND GROWTH OF MICROAEROPHILIC VIBRIOS - Fletcher, R. D. (1964)
Fletcher, R. D. (University of Connecticut, Storrs), and W. N. Plastridge. Gaseous environment and growth of microaerophilic vibrios. J. Bacteriol. 87:352–355. 1964.—Strains of microaerophilic vibrios from cattle, chickens, man, and sheep were placed in four groups on the basis of catalase and H(2)S production and glycine tolerance. By these tests group I was + − −, group II was + − +, group III was + + +, and group IV was − + +. On yeast extract-agar, the optimal oxygen level was 2.5% for group I, and 5.0% for the other three groups; the optimal carbon dioxide level was 10% for all four groups; the group I strains from man and sheep and the group II strains differed from the group I strains from cattle, by tolerating higher levels of both oxygen and carbon dioxide. On a chemically defined medium, the optimal oxygen level was 1.0%, and the optimal carbon dioxide level was 10% for groups I and II; the group II strains were more sensitive to high levels of carbon dioxide than were group I strains from cattle.